2020
DOI: 10.1111/apt.16206
|View full text |Cite
|
Sign up to set email alerts
|

Phenome‐wide association study in adult coeliac disease: role of HLA subtype

Abstract: SummaryBackgroundCoeliac disease arises in genetically susceptible individuals, in particular in carriers of HLA‐DQ2/DQ8 risk alleles and is associated with various comorbidities. Coeliac disease may confer an increased mortality, but the data are conflicting.AimsWe aimed to characterize mortality and morbidity in patients with coeliac disease with a special focus on the role of the number of HLA risk alleles.MethodsWe studied coeliac disease‐associated morbidity and mortality in ~500 000 participants of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…As shown in Figure 1, a literature search identified 5898 records, from which 25 eligible studies were identified 10–16,18,19,23–38 . Of these, seven were older reports 11–13,23–26 for which updated or more comprehensive reports on the same population of patients were available 10,16,27,30,31 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Figure 1, a literature search identified 5898 records, from which 25 eligible studies were identified 10–16,18,19,23–38 . Of these, seven were older reports 11–13,23–26 for which updated or more comprehensive reports on the same population of patients were available 10,16,27,30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…A post‐hoc analysis of cause‐specific mortality in dermatitis herpetiformis showed reduced mortality from cardiovascular diseases (pooled HR 0.70, 95% CI 0.53–0.92) and no increase in mortality from malignancies overall (pooled HR 0.87, 95% CI 0.62–1.23). Four studies reported outcomes on cause‐specific mortality in undiagnosed coeliac disease 19,28,32,33 . However, as the sample size of studies on undiagnosed coeliac disease was generally small, no further analysis on cause‐specific mortality in these patients was possible.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations